2021
DOI: 10.1029/2020jb021339
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bearing Amphiboles, Aqueous Fluids, and Melts in Subduction Zones: Insights on Halogen Cycle From Electrical Conductivity

Abstract: Amphiboles are hydrous minerals present in the altered oceanic crust and play a vital role in transporting hydrophile elements including halogen into the deep mantle via subduction of oceanic plates (Debret et al., 2016; Ito et al., 1983). The crystal structure of amphibole consists of corner-sharing tetrahedral units linked to form double chains and edge-sharing octahedral units. The octahedral strip is sandwiched between two tetrahedral double chains with their apices pointing toward each other forming an I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…Chen et al (2018) used thermal model predictions for various regions to understand the role of phengite dehydration on the formation of high conductivity anomalies above subducting slabs. Similar studies focusing on the influence of dehydration on the electrical conductivity of epidote (Hu et al, 2017), talc (Wang et al, 2020), NaCl-bearing aqueous fluids (Guo and Keppler, 2019), and glaucophane (Manthilake et al, 2021).…”
Section: Translation Of Mineral Physics To Geophysical Quantitiesmentioning
confidence: 86%
“…Chen et al (2018) used thermal model predictions for various regions to understand the role of phengite dehydration on the formation of high conductivity anomalies above subducting slabs. Similar studies focusing on the influence of dehydration on the electrical conductivity of epidote (Hu et al, 2017), talc (Wang et al, 2020), NaCl-bearing aqueous fluids (Guo and Keppler, 2019), and glaucophane (Manthilake et al, 2021).…”
Section: Translation Of Mineral Physics To Geophysical Quantitiesmentioning
confidence: 86%
“…In comprehensive comparisons with previously acquired electrical conductivity results on the hot-pressed sintering polycrystalline quartz reported by Bagdassarov and Delépine (2004) [113], synthetic polycrystalline anorthite reported by [60], as well as the pure aqueous fluid of sodium chloride with the 5% of weight percentage reported by Sinmyo and Keppler (2017) [114], one new origin for the explanation of high conductivity anomaly at the depth ranges from 70 to 120 km was put forward on the base of the released water-bearing fluid during the process of epidote dehydration at high temperature and high pressure. Furthermore, some recently reported electrical conductivity and elastic wave velocity results on hydrous halogen-bearing amphibole, glaucophane, Liebermannite, chlorite, and lawsonite from Manthilake et al [98][99][100][101][102] also confirmed that the dehydration of hydrous minerals will release a large amount of the water-bearing fluids, which can be used to reasonably explain the anomalously seismic and electrical transport behaviors in the region of hot subduction of deep mantle wedges.…”
Section: Electrical Conductivity Of Hydrous Epidotementioning
confidence: 91%
“…It is well known that the electrochemical AC impedance spectroscopy method is one of most efficient technique to measure the electrical conductivity of hydrous minerals and rocks at conditions of high temperatures and high pressures [98][99][100][101][102][103][104][105][106]. Before we launched a complex impedance spectroscopy measurement, the AC signal voltage ranges from 10 mV to 3 V and the scanning frequency ranges from 10 −5 Hz to 3.2 × 10 7 Hz need to be predesignated by virtue of Z-Plot program in the complex impedance spectroscopy analyzer.…”
Section: Experimental Theory and Measurement Methodsmentioning
confidence: 99%
“…The positive δ 37 Cl of EDM1 could reflect the breakdown of amphiboles from the upper slab lithologies. A recent study on electrical conductivity shows amphibole to be one of the principal hosts of Cl in the slab (Manthilake et al, 2021). Amphibole as residual phase during slab dehydration in low temperature subduction zones has been invoked to explain extremely low Cl and F in melt inclusions (Iwate; Rose-Koga et al, 2014) because it holds on to these halogens and it explains why they are subsequently less abundant in the melt.…”
Section: Magma Sources Of Chlorine Beneath Strombolimentioning
confidence: 99%